Recent Advances In Oral Potentially Malignant Disorders: A Therapeutic Perspective From An Oral And Maxillofacial Clinician And Pathologist – A Systematic Review - Shunmugavelu, Karthik; Suganya, S.; MDS, L. Jeevanandam; Saheb, Samiullah Dowlath (Journal of Neonatal Surgery, 2025)
Oral potentially malignant disorders (OPMDs) are recognized precursors to oral squamous cell carcinoma (OSCC) and pose a major diagnostic and therapeutic challenge. This systematic review critically synthesizes recent advances in the classification, diagnosis, molecular pathology, viral associations, and therapeutic management of OPMDs. Systematic literature review according to PRISMA guidelines selected 8 major studies between 2021 and 2025. Developing evidence from literature points toward the role of advanced classification systems, artificial intelligence-guided diagnostics, metabolomic profiling, microenvironmental modulation, and viral oncogenesis in enhancing early diagnosis and risk stratification. Challenges persist with standardization of diagnostic modalities, cross-population validation of biomarkers, and making new technologies universally accessible globally. An integrated multidisciplinary strategy that includes technological advancements and molecular understanding is needed to maximize preventive measures and minimize the global burden of oral cancer.